2021
DOI: 10.1021/acs.analchem.1c02023
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printed Dual-Mode Chemical Vapor Generation Point Discharge Optical Emission Spectrometer for Field Speciation Analyses of Mercury and Inorganic Selenium

Abstract: Due to the large size and high energy consumption of instruments, field elemental speciation analysis is still challenging so far. In this work, a portable and compact system device (230 mm length × 38 mm width × 84 mm height) was fabricated by using three-dimensional (3D) printing technology for the field speciation analyses of mercury and inorganic selenium. The device comprises a cold vapor generator, photochemical vapor generator, and miniaturized point discharge optical emission spectrometer (μPD-OES). Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…The final paper covered this section on Hg speciation in waters reports on the use of 3D printing to fabricate a field portable CV and photo-chemical vapour generator (PVG) μ-point discharge (PD)-OES instrument. 121 The system was compact with a total dimension of 230 × 38 × 84 and a complete description on the design and fabrication of the system is given in the paper and ESI. For Hg speciation, iHg was selectively reduced to Hg 0 with 0.001% (m/v) KBH 4 and 5% (v/v) HCl whereas the reduction of both iHg and MeHg was obtained by PVG in presence of formic acid and using a nano-TiO 2 coated quartz coil.…”
Section: Elemental Speciation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The final paper covered this section on Hg speciation in waters reports on the use of 3D printing to fabricate a field portable CV and photo-chemical vapour generator (PVG) μ-point discharge (PD)-OES instrument. 121 The system was compact with a total dimension of 230 × 38 × 84 and a complete description on the design and fabrication of the system is given in the paper and ESI. For Hg speciation, iHg was selectively reduced to Hg 0 with 0.001% (m/v) KBH 4 and 5% (v/v) HCl whereas the reduction of both iHg and MeHg was obtained by PVG in presence of formic acid and using a nano-TiO 2 coated quartz coil.…”
Section: Elemental Speciation Analysismentioning
confidence: 99%
“…The use of 3D printing to fabricate a field portable CV and photo-chemical vapour generator (PVG) μ-point discharge (PD)-OES instrument. 121 The system was compact with total dimensions of 230 × 38 × 84 and a complete description of the design and fabrication of the system was given in the paper and ESI. Selenium speciation was evaluated by PVG-μPD-OES in the presence of 50 mmol L −1 of nitrate and with and without adding nano-TiO 2 NPs.…”
Section: Elemental Speciation Analysismentioning
confidence: 99%
“…A three-dimensional printing prepared device was also reported for the field analysis of different inorganic Se species. 28 However, previous studies mainly focused on Se(IV) and Se(VI), and the determination of SeNPs was rarely reported. Though the direct speciation analysis of various Se species could be achieved by X-ray absorption near-edge structure spectroscopy, 29 the high detection limit and inaccessibility to the instrument hindered its wide applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Various methods such as ion-exchange chromatography (IEC), solid-phase extraction (SPE), , TiO 2 nanoparticle adsorption, , capillary electrophoresis, , and cloud point extraction (CPE) have been used to separate inorganic Se­(VI) and Se­(IV) in the aquatic system. A three-dimensional printing prepared device was also reported for the field analysis of different inorganic Se species . However, previous studies mainly focused on Se­(IV) and Se­(VI), and the determination of SeNPs was rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] Microplasma excitation sources include but are not limited to atmospheric pressure glow discharge (APGD), 20 electrolyte cathode glow discharge (ELCAD), 24,25 solution anode glow discharge (SAGD), 26 solution cathode glow discharge (SCGD), 27 dielectric barrier discharge (DBD) 28 and point discharge (PD). 29 Among them, APGD has attracted widespread attention in the eld of elemental analysis due to its compact structure, high stability and easy coupling. So far, APGD has been used in combination with various sampling systems and obtained satisfactory results.…”
Section: Introductionmentioning
confidence: 99%